The Evaluation of Athletes’ Achievement Coaching Program of Measurable Sports (Athletics, Weightlifting, Archery, and Swimming) in Lampung Province (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
This research aimed at: (1) evaluating the antecedent of athletes’ achievement coaching program of measurable sports which covered background (management, coach, and athletes), purposes, and coaching programs, (2) evaluating the transaction of athletes’ achievement coaching program of measurable sports which covered management board selection, coach selection, athlete selection, training program and appropriate working program, sources availability, and the availability of supporting facilities and infrastructures, (3) evaluating the outcomes of athletes’ achievement coaching program of measurable sports which covered coach performance or coaching results (medals results). This research used descriptive qualitative method by considering Countence Model of Stake which covers antecedents, transactions, and outcomes. Informants in this research were KONI management board of Lampung Province, provincial administrator of Lampung (Pengprov), coach, and athletes and parents. The results of the research: (1) Antecedent which covered equipment completeness was well structured, where there was clear management structure and the existence of athletes’ coaching program was clear, but it was not well programmed, (2) Transaction on the athletes’ coaching program of measurable sports in Lampung Province was not good, (3) Outcomes, in this case, the results were not good enough. Athletes’ achievements were less stable since they did not get medals every year and also they were not routinely participating in championships every year.